(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The genotoxicity of 5 samples of waters of r. Hrazdan and r. Marmarik were investigated with the use of Tradescantia clone 02 somatic mutations stamen hairs (SH) and micronucleus (MN) testing. It was found out that during the three months of investigation the highest level of somatic mutation was observed in SH watering from r. Hrazdan in Hrazdan city and in MN – from r. Hrazdan in Yerevan City. The results approve that the mentioned tests can be used to value the genotoxcity of water enviroment pollutants.